Characteristics of the L138ins (p.Leu138dup) mutation in Russian cystic fibrosis patients - Petrova, Nika V; Kashirskaya, Nataliya Y; Vasilyeva, Tatyana A; Kondratyeva, Elenai I; Marakhonov, Andrey V; Macek Jr, Milan; Ginter, Evgeny K; Kutsev, Sergey I; Zinchenko, Rena A (Journal of Medical Science, 2020)
The L138ins mutation, found in Russian cystic fibrosis (CF) patients, is a duplication of three nucleotides (CTA) in exon 4 of the CFTR gene and is categorised as a small in-frame insertion/deletion. As a result, the CFTR protein molecule elongates by one amino acid residue, leucine, at position 138 (codon 138 (CTA)). In accordance with the new nomenclature, it should be called c.411_412insCTA (p.Leu138dup). The c.411_412insCTA (p.Leu138dup, L138ins) mutation is found in CF patients of Slavic origin (Russians, Ukrainians) and has been linked to a single haplotype of the intragenic DNA markers IVS1CA-IVS6aGATT-IVS8CA-IVS17bCA - 22-7-16-13.
Keywords: cystic fibrosis; L138ins (c.411_412insCTA, p.Leu138dup) mutation; haplotype